Application of Co3O4-based materials in electrocatalytic hydrogen evolution reaction: A review. (21st August 2020) - Ma, Junqing; Wei, Huijie; Liu, Yong; Ren, Xinyuan; Li, Yixuan; Wang, Fei; Han, Xinyue; Xu, Enmin; Cao, Xiaoyu; Wang, Guangxin; Ren, Fengzhang; Wei, Shizhong
Abstract: Environmental pollution and energy shortage make the development of clean energy more and more urgent. As a kind of clean renewable energy, hydrogen have attracted great attentions in recent years. Recently, Co3 O4 -based materials have emerged as promising candidates for electrocatalytic hydrogen evolution reaction (HER), due to their attractive electrocatalytic activity, low cost as well as the electrochemical durability, which make it attract widely attentions. In this review, we summarize the application of Co3 O4 -based materials in electrocatalytic HER, including pure Co3 O4, the doped Co3 O4 and the Co3 O4 -based composite materials. Furthermore, the strategies to enhance their electrocatalytic performance are summarized and discussed, such as morphological engineering, doping, as well as compositing with other materials. Finally, the limitation and challenges of Co3 O4 -based materials for HER, as well as their prospects for future research, are proposed. We believe that this review will be helpful for scientists to seek promising HER electrocatalytic materials. Graphical abstract: Image 1 Highlights: The application of Co3 O4 -based electrocatalysts in H2 evolution is summarized. The various modification strategies of Co3 O4 -based electrocatalysts are reviewed. Challenges and future prospects of Co3 O4 -based electrocatalysts are proposed.